ORGANIZATIONAL TRANSFORMATIONS IN ENTERPRISE ACTIVITY: ROLE AND RESEARCH IN MODERN CONDITIONS - KAZMIN, Illia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Organizational transformations play a pivotal role in a company’s development and competitiveness in the modern world. They encompass a variety of changes in structure, processes, corporate culture, and strategy. These changes are not just about adaptation but about increasing efficiency and adaptability, enhancing the company’s potential for growth and resilience in the face of external challenges. The article aims to study the role and consequences of these transformations in the enterprise’s activity in modern conditions. It was determined that the development processes of each enterprise in modern realities are associated with continuous organizational changes and subsequent adaptation to them. It has been proven that in the fast-moving and unstable economic environment of Ukraine, organizational changes become not only relevant but also necessary for the survival and development of enterprises. This connection defines the prerequisites for the enterprise’s organizational transformations. Attention is focused on the fact that assessing the consequences of organizational transformations at the enterprise is a rather complex task that requires various indicators. The choice of their list depends on the specifics of business activity and the nature of transformations. The leading indicators are proposed to be divided into financial, operational, organizational, and other categories specific to a specific industry or enterprise. It has been proven that in modern conditions, enterprise transformations can have significant advantages and disadvantages. The positive and negative sides of the changes foreseen in organizational transformations are studied. In order to ensure such an analysis, development indicators and markers of the transformation process should be clearly defined at the stage of change planning. Their presence provides tools for measuring progress, identifying problems, and evaluating the effectiveness and feasibility of making management decisions, ultimately contributing to achieving the company’s strategic goals.